Una nueva localidad de Pinus discolor Bailey & Hawksworth en el centro de México - Zavala Chavez, Fernando; Campos Diaz, Jose Luis (Instituto de Ecología, A.C., 1993)
The presence of Pinus discolor Bailey & Hawksworth is reported from a new locality in México: in the east-central part of the State of Querétaro. The Southern limit of the known distribution of that species reached latitude 22° 02’ N in the southwestern part of the State of San Luis Potosí; with this report this limit is now extended down to latitude 20° 50’ 45” in México.